2011
DOI: 10.1530/eje-11-0408
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cardiac disease in newly diagnosed patients with acromegaly: results of a 10 year survey study

Abstract: Context: The most frequent cause of death in acromegaly is cardiomyopathy. Objective: To evaluate determinants of acromegalic cardiomyopathy. Design: Observational, open, controlled, retrospective study. Subjects: Two hundred and five patients with newly diagnosed active acromegaly (108 women and 97 men; median age 44 years) and 410 non-acromegalic subjects sex-and age-matched with the patients. Main outcome measures: Left ventricular (LV) mass index (LVMi), transmitral inflow early-to-atrial (E/A) peak veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 34 publications
5
62
0
1
Order By: Relevance
“…Conflicting data exist about the effect of acromegaly on lipid levels. Some studies indicate a worse lipid profile in active acromegaly (9,24) while other authors reported better values (22,25,26) and a worse profile after therapy (26). We found total cholesterol and triglycerides to be significantly lower both in controlled and non-controlled acromegaly.…”
Section: Discussionsupporting
confidence: 38%
“…Conflicting data exist about the effect of acromegaly on lipid levels. Some studies indicate a worse lipid profile in active acromegaly (9,24) while other authors reported better values (22,25,26) and a worse profile after therapy (26). We found total cholesterol and triglycerides to be significantly lower both in controlled and non-controlled acromegaly.…”
Section: Discussionsupporting
confidence: 38%
“…21) Concordant with our study, patient age was found to be the most important predictor of LVDD in acromegaly in a recent survey study with a large sample size. 22) Hypertension and LVH are major determinants of LVDD. Cardiac walls are thickened, but cardiac chambers are rarely enlarged, an event resulting from the relative increase in cardiac myocyte width, due to the parallel assembling of new contractile protein units.…”
Section: Discussionmentioning
confidence: 99%
“…Scattered spots and flaky hyperintensity in T1 and T2, apparently normal heart. 13 Therefore, when occurrences of clinical arrhythmias and heart failure are not easily explained by cardiogenic causes, it seems reasonable to consider the possibility of acromegaly-associated cardiovascular complications.…”
Section: Case Reportmentioning
confidence: 99%